Ecosystem Difficulties and the Performance of Fisheries Management Systems - Chidiegwu; Hamisu (Advances in Aquaculture and Fisheries Management, 2025)
This paper has three objectives. It first provides a brief update of data from a 1997 research by the Organization for Economic Co-operation and Development (OECD) that demonstrated which management strategies are most effective in protecting marine fisheries and producing significant social and economic benefits. According to the original OECD report, individual fishing quotas are a good approach to restrict the number of people participating in a fishery, control exploitation, ameliorate the consequences of race-to-fish and most of its attendant effects, and create resource rent and enhanced profitability. Additionally, it discovered that a race-to-fish and all of its consequences result from competitive TAC management. Furthermore, even though conservation may have suffered in their absence, the OECD statistics demonstrated that area and time closures have not been effective in ensuring resource conservation. The update indicates that most of the original findings remain valid. The second objective is to report on current policy changes since 1995, with a focus on ecosystem-based management approaches. These include large marine ecosystem (LME) programs, marine protected areas (MPAs), and habitat protection initiatives. The third subject discussed in the paper is the governance concerns of ecosystem-based fisheries management. The report argues that the political marketplace that determines fisheries management policy usually disadvantages conservation and long-term economic benefits. The article concludes with suggestions for strengthening our fishery governance systems.